Specialists’ learning from facilitating group peer telementoring: a qualitative study - R. Sam Larson; James W. Dearing; Nagesh Rao; Caryn E. Medved (BMC Medical Education)
Abstract Background Group peer telementoring supports interprofessional learning through multi-directional and synchronous engagement where experienced and knowledgeable individuals exchange guidance and support with differently experienced and knowledgeable individuals. A leading example of group peer telementoring among medical specialists and medical generalists is Project Extension for Community Healthcare Outcomes (Project ECHO), a rapidly spreading program with demonstrated learning outcomes among community-based medical generalists. Yet the multi-directional exchanges that characterize group peer telementoring interactions suggest that specialists facilitating sessions may also learn from the group experiences. We explored what medical specialists learn from community-based medical generalists and from other specialists as a result of facilitating and participating in group peer telementoring. Methods Pairs of ECHO administrative staff and researchers interviewed medical specialists who facilitated Project ECHO work. Using interview transcripts, we identified 129 learning episodes in which 53 specialists discussed what they learned from their Project ECHO experiences. An inductive multi-phase thematic analysis was used to identify what medical specialists were learning and from whom. Results Three primary themes emerged from the data. Specialists learned about community-based health care, including learning about unique and novel community-based treatments and patient needs. Specialists broadened and deepened their knowledge of patient care, including taking an interprofessional view and learning more about their own specialty area. Specialists also learned about learning, including revelations about power hierarchies, the importance of opening space for learning, and practicing humility. Conclusions Project ECHO’s emphasis on group peer telementoring brought the realities of community-centric care to the attention of medical specialists, deepening their knowledge about patient care and about learning. Specialists learned from community-based medical generalists, other medical specialists within their discipline, and from medical specialists with other expertise. The "all teach, all learn" space that medical specialists endeavored to create in Project ECHO for community-based medical generalists created a safe space for specialists to admit what they did not know. Continued facilitation and participation in group peer telementoring may provide medical specialists with feedback about diagnoses, treatments, and community-based resources for low-income rural and inner-city patients that contributes to their continued development and medical education.